The Influence of the Demonstration Method with the Help of Geogebra Software on the Ability to Understand Mathematical Concepts - Abqoriyah Nur Azizah; Fitria Zana Kumala (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
The background of this research is the inability of students to understand mathematical concepts. The researcher chose the demonstration method with the help of GeoGebra Software to overcome the lack of understanding of mathematical concepts. The purpose of this research is to find out whether there is an effect of the demonstration method with the help of GeoGebra Software on the ability to understand mathematical concepts. This research is a Quasi-experimental study where the design applied is Nonequivalent Control Group Design. The population of this study were 79 students of class IX at SMP Muhammadiyah 2 Purwokerto. The research sample consisted of 26 students from class IXA which were used as the experimental class and 27 students from class IXB which were used as the control class. The test instrument is used to measure the ability to understand each student's mathematical concepts. The N-Gain test shows that the control group has an average N-Gain of 0.29 which is in the low category, while the experimental group has an average N-Gain of 0.61 which is in the medium category. The average difference in the percentage of pretest and posttest scores on all indicators of mathematical understanding ability in the control class was 9.75% while in the experimental class was 13.68%. From the t test, the value of sig = 0.004 < α = 0.05 means that there is a difference in the average N-Gain value of the experimental class and the average N-Gain value of the control class. The conclusion from this study is that there is an influence of the demonstration method with the help of GeoGebra Software on the ability to understand mathematical concepts in class IX SMP Muhammadiyah 2 Purwokerto.